Relações de gênero e ensino de matemática: uma análise do projeto as “minas” da matemática - Rodrigues, Duciâny Batista da Silva (Universidade Federal do Tocantins, 2021)
The present work talks about gender relations and Mathematics teaching, the role of the school in this scenario and how teachers can contribute to the reduction of inequalities and differences between genders, inside and outside the school environment. An analysis is made of the meetings of the project The “Minas” of Mathematics, seeking to present a pedagogical practice that aims to promote the exchange of knowledge of mathematical concepts with an exclusively female target audience, of all ages, with a view to improving learning, enabling progress in school performance, both in mathematics and in other subjects. Favoring the personal growth of each student, giving them tools for increasing self-esteem and for professional and academic growth. Each meeting is divided into three moments: in the first, the theme deals with empowerment; in the second, activities involving Mathematics contents are worked on; and finally the theme is about professions. As a stimulus, to the permanence and enjoyment of the meetings, motivational prizes donated by local partners are offered. Our research question is how to propose, develop and rethink actions that make it possible to teach mathematics devoid of prejudice in gender relations, imposed by social relations, which generate inequalities and, especially, the inferiorization of women? To answer this question, we established as a general objective to analyze the actions carried out in the project The “Minas” of Mathematics, in the light of the theoretical framework, with a view to perceiving which influenced and promoted emancipation and learning in mathematics, in addition to empowering and strengthening women as an active subject in the construction of society. As specific objectives we chose: to carry out a survey of the actions developed in the project The “Minas” of Mathematics; analyze the data collected from the actions developed in the project; rethink project methodologies based on data analysis. Given the importance of rethinking gender relations and teaching Mathematics, there is a need to build pedagogical practices that encourage respect for differences and that promote conditions of equal mathematical learning for genders. With the action research methodology, it was possible to identify flawed points in the execution of the actions, causing a reflection and a new proposal to achieve the project's objectives through activities related to the socio-cultural practices of the participants, making use of Ethnomathematics as a guiding element. Women mathematize and teach mathematics from generation to generation through their daily practices, whether schooled or not. Women are active agents in building themselves, their families and society. A latent desire in the final steps of this research is that the actions of the project The “Minas” of Mathematics evolve and collaborate with the teaching of school mathematics through mathematics built on socio-cultural practices. Better than discovering the flaws in our practices is the opportunity for evolution.